ANALISIS PENEMPATAN PEGAWAI NEGERI SIPIL PADA BADAN KEPEGAWAIAN DAERAH KOTA PEKANBARU - ", Rini; Khairani, Tuti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Placement of the right employees are the way to optimize the capabilities, skills to the job performance of employees, it is an evolution of employee future directed to place employees in positions appropriate to their rules and their qualifications, but in reality there are still some institutions, especially government that ignores those principles. Employees are very important and key to any organization because employees determine the realization of the objectives of the organization, so that the objective will be easily achieved if the employee is placed at a position corresponding to the competency. The purpose of this study was to determine the placement of Analysis of Civil Servants at the Regional Employment Board Pekanbaru city and to determine the factor that influence it. The concept of the theory is used the staffing proposed by siagian three promotions, and demotions over the task. This study is using current methods of qualitative research with an assessment of descriptive data. In data collection the author uses interview, observation and documentation. By using key informants as source of information and triangulation techniques as source of data validity. The results of research by the author that the Placement Analyze On Civil Servants Personnel Board in Pekanbaru, placement is done as in the Regional Employment Board of Pekanbaru most positions occupied by most employees are not in accordance with the educational background. In addition, factors are affecting the Regional Employment Board of Pekanbaru is the employees placement who are still influenced elements are not objective, the proximity of families and certain groups. This study is focused on the placement of employees on the basis of expected employees more motivated and passion in order to gain new positions and tasks through a system of career coaching orderly and healthy to realize an apparatus and accountable government organization and quality. Key words: Human Resource Management, Job Analysis, Placement employee